KM3NeT/ARCA expectations in view of a novel multimessenger study of starburst galaxies. (13th December 2021) - Marinelli, A.; Ambrosone, A.; Ibnsalih, W.I.; Miele, G.; Migliozzi, P.; Pisanti, O.; Sharma, A.; Ageron, M.; Aiello, S.; Albert, A.; Alshamsi, M.; Alves Garre, S.; et al.
Abstract: Starburst galaxies (SBGs) and more in general star-forming galaxies represent a class of galaxies with a high star formation rate (up to 100 M ⊙ /year). Despite their low luminosity, they can be considered as guaranteed "factories" of high energy neutrinos, being "reservoirs" of accelerated cosmic rays and hosting a high density target gas in the central region. In this contribution we present a novel multimessenger study of these sources and the possibility of observing their neutrino signals with the KM3NeT/ARCA telescope. The differential sensitivity for different SBG scenarios is reported considering track-like neutrino events in the 100 GeV–100 PeV energy range.